ASPEK FISIK DASAR DALAM PENENTUAN ARAHAN KESESUAIAN LAHAN PADA RENCANA TATA RUANG WILAYAH KABUPATEN BANGKA SELATAN - Suganda, Bombom Rachmat (Bulletin of Scientific Contribution, 2009)
Land use in spatial planning, often forgetting that the land carrying capacity refers to the thematic maps. The number of land suitability analysis on spatial planning that is not appropriate, and often result in the basic physical problems. Basic physical problems will interfere the facilities and infrastructure which supporting economic activity, resulting in financing that sometimes is not economical.